2020
DOI: 10.1007/s42452-020-03551-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of persistent organic pollutants: dioxins, furans, and their associated nitrogenated analogues

Abstract: Dioxins and furans are no doubt the most notorious class of organochlorine toxicants in the environmental system whose adverse effects are detrimental to public health with extreme negative economic impacts. Polychlorinated dibenzop-dioxin and dibenzofurans and dioxin-like compounds such as the polychlorinated biphenyls, carbazoles are in the class of persistent organic pollutants-prioritized under the Stockholm convention as the "dirty dozens", besides being listed as group 1 human carcinogens by the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 135 publications
0
10
0
Order By: Relevance
“…Presently, 17 congeners are highly toxic and are considered A1 carcinogens, with 2,3,7,8-tetra chloro-dibenzo-para-dioxin (2,3,7, [TEF = 1 (LD 50 = 0.04 mg kg À1 )] being identified as one of the most toxic compound. 1 However, it should be noted that D&Fs do not occur naturally and are mainly products of different incineration processes having a chlorine source together with combustion, industrial, and reservoir sources. [2][3][4] PCDDs and PCDFs are A1 carcinogens and owing to their high toxicity, high biological half-life, high environmental persistence, bioaccumulation, and carcinogenicity, should not be present in the atmosphere, and hence they need to be either completely degraded or mineralized to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, 17 congeners are highly toxic and are considered A1 carcinogens, with 2,3,7,8-tetra chloro-dibenzo-para-dioxin (2,3,7, [TEF = 1 (LD 50 = 0.04 mg kg À1 )] being identified as one of the most toxic compound. 1 However, it should be noted that D&Fs do not occur naturally and are mainly products of different incineration processes having a chlorine source together with combustion, industrial, and reservoir sources. [2][3][4] PCDDs and PCDFs are A1 carcinogens and owing to their high toxicity, high biological half-life, high environmental persistence, bioaccumulation, and carcinogenicity, should not be present in the atmosphere, and hence they need to be either completely degraded or mineralized to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, 17 congeners are highly toxic and are considered A1 carcinogens, with 2,3,7,8-tetra chloro-dibenzo- para -dioxin (2,3,7,8-TCDD) [TEF = 1 (LD 50 = 0.04 mg kg −1 )] being identified as one of the most toxic compound. 1 However, it should be noted that D&Fs do not occur naturally and are mainly products of different incineration processes having a chlorine source together with combustion, industrial, and reservoir sources. 2–4…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, forest fires can alter soil properties and the structure of microbial communities [9]. For instance, it has recently been reported that the combined effect of fire and the presence of chromium affects soil microbial communities [10], whereas toxics compounds such as dioxines or furanes are released into the environment by forest fires [11,12]. These substances can also alter the metabolism of soil microbiota [13].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, they can accumulate in the fatty tissue of living organisms including humans, and are found at higher concentrations at higher levels in the food chain [ 4 , 5 ]. They are also toxic to humans and wildlife, and are widely associated with adverse effects on growth, development, reproduction, and survival [ 6 ]. For example, polycyclic aromatic hydrocarbon (PAH), which is a kind of common POPs, is classified as possible or probable human carcinogens [ 7 ].…”
Section: Introductionmentioning
confidence: 99%